A meta-analysis suggests climate change shifts structure of regional communities of soil invertebrates. (June 2023) - Goncharov, Anton A.; Leonov, Vladislav D.; Rozanova, Oksana L.; Semenina, Eugenia E.; Tsurikov, Sergey M.; Uvarov, Alexei V.; Zuev, Andrey G.; Tiunov, Alexei V.
Abstract: Soil animals perform a range of essential ecosystem functions and can modify the effects of global change on terrestrial ecosystems. We evaluated responses of six major groups of soil animals (Acari (all groups), Oribatida, Collembola, Insecta, Nematoda, and Oligochaeta) to controlled changes in air temperature, precipitation level or carbon dioxide concentration by using random-effects modelling and mixed-effects meta-regression modelling. Along with the three global change factors, sixteen local climatic characteristics (such as mean annual temperature, Köppen climate classification, vegetation type) were tested. Overall, 86 studies comprising 236 observations with mean duration of 51 months were selected as relevant for the analysis. Quantitative links between global change factors, local climate characteristics and changes in abundance of four taxonomic groups of soil animals were revealed. Warming and precipitation level were associated most strongly with population dynamics of soil invertebrates compared to elevated atmospheric CO2 . Each 1 °C increase in air temperature was correlated with a mean of 12.5% (95% CI: 2.5%–22.6%) increase in Acari abundance, while populations of Collembola were declined by 9.6% (95% CI: −17.8% to −1.4%). Meanwhile, each 10% increase in precipitation level was correlated with the increase in the abundance of Nematoda by 1.4% (95% CI: −7.6% to 10.4%) and Oligochaeta by 34.7% (95% CI: 8.1%–61.2%). Considering IPCC estimates (SSP3-7.0 Scenario) of an average climate warming by 3.6 °C and a substantial variation in local precipitation levels (up to ±20%) by the end of the 21st century, strong local changes in the structure of detrital food webs are predicted by meta-regression models. In regions with decreased precipitation, the formation of soil food webs promoting carbon mineralization may be expected, while in regions with increased precipitation, the changes in detrital food web structure can contribute to the accumulation of carbon in the soil. Highlights: Responses of soil invertebrates to major climate change factors were studied by meta-analysis. Warming and precipitation levels better predicted soil fauna responses than elevated CO2 levels. Each 1 °C increase correlated with 12.5% of Acari abundance increase. Each 1 °C increase correlated with 9.6% of Collembola abundance decrease. By yr 2100, strong regional changes in structure of detrital food webs were predicted.